Introduction of E-commerce to the MSME trading business community at the MMTC supermarket center - Ihdina Gustina; Dedy Lazuardi; Putri Wahyuni; Adek Apriyandi (Outline Publisher, 2024)
This activity aims to understand the impact of e-commerce developments on MSME players, especially in the aspects of market access, operational efficiency, business growth and the challenges they face. This activity provides insight for MSME players in making more informational and strategic decisions in facing the e-commerce era. In this mini research, we used the qualitative activity method. Where for these activities we go directly to the field to see the actual situation, then we can conduct interviews directly with MSME actors. In this activity, we interact directly with our respondents and the situations we observe. We chose this research method because we can see directly the facts about the material we want to research. The results of our activities reveal that not all MSME business owners experience positive impacts or good changes in the development of e-commerce. In this activity, it was also found that e-commerce, which was supposed to provide changes in the national economy, instead turned around by plunging several MSME players into tight and dangerous competition. Uneven penetration or introduction of business technology, limited capital, ideas, innovation and lack of digitalization in some MSMEs make this problem complex and complicated. Another thing that needs to be highlighted is that intense competition and changes in models and people's tastes are quite complex challenges for MSME players.